(untitled) (Research, Society and Development, 2021)
The present study aimed to outline the scenario of a clinical imaging exam using organizational diagnostic tools. The tools used, for having tested and proven scientific rigor, help to better visualize the scenario of an organization. For the present study, the Management Excellence Model (MEG) and the GUT Matrix were used. The methodological framework of the study is of an applied nature, being a case study, descriptive and of a qualitative and quantitative character, based on questionnaires applied to the manager of an image exam clinic, whose name will be kept confidential. The results found pointed to a deficient management, which needs better design, mainly through better management development actions and improvement of the organization’s internal processes. Finally, although problems have been detected at the management level, it is important to emphasize the need to seek a better view of the organization, through other tools that view the perspective of customers and employees, for example, so that the problems found in the present study can be solved in the best possible way.